Colloids of Holey Gd2O3 Nanosheets Converted from Exfoliated Gadolinium Hydroxide Layers. Issue 36 (5th August 2018) - Jeon, Ki‐Wan; Zhang, Luojiang; Choi, Seonyeong; Lee, In Su
Abstract: This paper proposes a confined solid‐state conversion approach using layered metal‐hydroxides for the production of a colloidal suspension of porous 2D crystalline metal oxide layers with superior electrochemical H2 O2 sensing performance. This study investigates the conversion chemistry of delaminated layers of gadolinium hydroxide (LGdH), [Gd2 (OH)5 ] +, encapsulated in a silica nanoshell that provides an antistacking and antisintering environment during the phase‐transition at high temperature. Thermal treatment of the LGdH layers within the protected environment results in a dimensionally confined phase‐transition into crystalline Gd2 O3 nanosheets with an isomorphic 2D structure. Furthermore, annealing at higher temperatures leads to the evolution of in‐plane mesoporous structure on the Gd2 O3 nanosheet. Based on insight acquired from in‐depth investigation, the evolution of in‐plane porosity proceeds through the in‐plane dominant silicate‐formation reaction at the interface with the surrounding silica shell. Their 2D‐anisotropic and mesoporous morphological features are preserved, producing a colloidal suspension of holey nanosheets that can be used to fabricate a thin and porous film through wet‐coating deposition. This study also demonstrates the superior electrochemical H2 O2 sensing ability of the resultant porous Gd2 O3 film, which represents a ≈1000‐ and 10‐fold enhancement of the detection limit and sensitivity, respectively, in comparison to previously reported Gd2 O3 films. Abstract : The confined conversion approach with exfoliated gadolinium hydroxide layers within a silica nanoshell produces a colloidal suspension of holey Gd2 O3 nanosheets that features a highly 2D‐anisotropic morphology with a few‐nanometer thickness and a unique in‐plane mesoporosity. The use of the resultant suspension allows for the fabrication of a porous Gd2 O3 film with superior electrochemical H2 O2 detection ability.